The need to minimize personnel resistance to innovative changes in the management system of a high-technological enterprise - N. N. Trofimova (Управление)
The article considers ways to minimize resistance to innovations in the management system of a high-tech enterprise. It has been shown that a decrease in the level of resistance of personnel to innovations can be achieved through the use of certain measures that contribute to the gradual preparation of the workforce of an enterprise for the implementation and implementation of the planned innovations. The concept of “personnel resistance” has been clarified. Based on empirical research, various categories of personnel resistance to  innovation have been analysed, signs of personnel resistance in the management system of a high-tech  enterprise have been highlighted. Possible reactions of personnel in cases of personnel resistance to innovative changes in the management system of a high-tech enterprise have been investigated. Special attention is paid to the reasons for the emergence of resistance in situations of innovation implementation. The use of an integrated author’s approach, based on the methods of scientific generalization, comparative analysis, systemic and situational approach, made it possible to establish the main consequences of the resistance of the personnel of hightech enterprises to socio-economic, organizational, managerial and technological innovations, taking into account their influence on the formation of the innovative potential of the organization. High-tech enterprises were offered to introduce a subsystem for managing personnel resistance to innovations in the general management system.The scientific novelty of the research lies in the fact that the author, on the basis of the research conducted, has developed a set of measures, the implementation of which in the context of the innovative development of a high-tech enterprise will significantly minimize the resistance of personnel in the management system of a high-tech enterprise. The practical significance of the work done is in the fact that it can serve as a basis for further scientific research in the field of personnel resistance management for an individual enterprise, taking into account the specifics of its activities in the field of innovative development.